2008
DOI: 10.1177/1538574407309316
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Continuous AutoTransfusion System (C.A.T.S) in Open Abdominal Aortic Aneurysm Repair: An Observational Comparative Cohort Study

Abstract: The use of the Continuous AutoTransfusion System (C.A.T.S; Fresenius Hemotechnology, Bad Homburg v.d.H., Germany), which conserves allogenic blood, is reported in 187 patients having abdominal aortic aneurysm repair during a 9-year period. Patients were allocated to C.A.T.S if a Haemovigilance technician was available. A mean of 685 mL of retrieved blood was reinfused in 101 patients receiving C.A.T.S; 61% required 2 U or less. All control patients required 3 U or more of allogenic blood. Allogenic transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
10
0
5
Order By: Relevance
“…In the emergent surgery of traumatic thoracic injury-induced bleeding, autologous blood transfusion is more time-saving, more convenient, safer and more effective than the stored blood transfusion, 9 and the patient's intraoperative blood loss will not be wasted. Moreover the former is fresh autologous RBCs with a better cell viability and higher oxygen carrying capacity, which can rapidly supply blood volume and maintain an effective cycle without adverse transfusion reactions 10 . But the indications and contraindications for autologous blood transfusion should be well known.…”
Section: Discussionmentioning
confidence: 99%
“…In the emergent surgery of traumatic thoracic injury-induced bleeding, autologous blood transfusion is more time-saving, more convenient, safer and more effective than the stored blood transfusion, 9 and the patient's intraoperative blood loss will not be wasted. Moreover the former is fresh autologous RBCs with a better cell viability and higher oxygen carrying capacity, which can rapidly supply blood volume and maintain an effective cycle without adverse transfusion reactions 10 . But the indications and contraindications for autologous blood transfusion should be well known.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that intraoperative cell salvage was beneficial for patients who had intraoperative blood losses of 1000 ml or more and Cell Saver volumes returned of 750 ml or more. Tawfick et al [14] published a retrospective cohort study with 187 patients who underwent open repair of AAA. One group of patients received an autotransfusion system (cell salvage) and the second group allogeneic transfusion.…”
Section: Retrospective Studies With Icsmentioning
confidence: 99%
“…Based on the results of these papers, only one study among the randomized studies confirmed the convincing benefit of using the cell salvage technique (Mercer [11]) and only 2 non-randomized studies (Quriel [6]-unwashed filtered blood, Tawfick [14]) provided similar results ( Table 1).…”
Section: Conclusion Regarding Randomized and Retrospective Studies Wimentioning
confidence: 99%
“…Šis metodas dažniausiai naudojamas šir-dies chirurgijoje, kraujagyslių chirurgijoje, ortopedinių operacijų metu, persodinant organus, kai kurių traumų metu (10,11,15,17,19,20,23).…”
Section: Perioperacinė Kraujo Reinfuzijaunclassified
“…Intraoperacinis kraujo perpylimas taikomas ir kitų operacijų, susijusių su dideliu kraujo netekimu, metu: kepenų persodinimo, splenektomijos, kai kurių traumų atveju. Daugeliui ligonių, kuriems daromos operacijos, šis metodas teikia neabejotinos naudos, ypač jei donorinio kraujo perpylimas yra negalimas arba nepakankamas (15,17,19,(22)(23)(24)(25).…”
Section: Intraoperacinė Kraujo Reinfuzijaunclassified